The Changing Returns to Crime: Do Criminals Respond to Prices?. (22nd January 2018) - Draca, Mirko; Koutmeridis, Theodore; Machin, Stephen
Abstract: To what extent does crime follow the pattern of potential gains to illegal activity? This article presents evidence on how criminals respond to this key incentive by reporting crime–price elasticities estimated from a comprehensive crime dataset containing detailed information on stolen items for London between 2002 and 2012. Evidence of significant positive crime–price elasticities are shown, for a panel of 44 consumer goods and for commodity related goods (jewellery, fuel, and metal crimes). The reported evidence indicates that potential gains are a major empirical driver of criminal activity and a crucial part of the economic model of crime. The changing structure of goods prices helps to explain over 10–15% of the observed fall in property crime across all goods categories, and the majority of the sharp increases in the commodity related goods observed between 2002 and 2012.